Blockchain and Machine Learning Powered Secure Online Voting System - Prof. S.M.Bankar; Dr. D.O.Patil; Krishna Bhand; Pooja Khachane; Karina Mane (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project report introduces a robust and scalable online voting system that leverages blockchain technology, machine learning, and facial recognition to overcome common issues related to electoral security, transparency, and accessibility. Traditional voting methods are often vulnerable to identity theft, voter impersonation, and data manipulation—threats that compromise the integrity and credibility of election outcomes. By incorporating blockchain, the system ensures that each vote is permanently and securely recorded on a decentralized ledger, preventing unauthorized alterations and enhancing transparency. The report outlines the system’s technical architecture, including the implementation of smart contracts for automatic vote verification and tallying. It also explains the secure handling and encryption of biometric data stored on the blockchain. Furthermore, the report discusses the key advantages, limitations, and future development opportunities of the platform. The proposed solution demonstrates a significant advancement in digital voting, offering a secure, transparent, and accessible alternative to conventional methods. Its potential applicability spans across large-scale elections in governmental bodies as well as decision-making processes in private organizations.